2021
DOI: 10.1126/sciadv.abi9787
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptome of early hematopoiesis guides arterial endothelial-enhanced functional T cell generation from human PSCs

Abstract: Hematopoietic differentiation of human pluripotent stem cells (hPSCs) requires orchestration of dynamic cell and gene regulatory networks but often generates blood cells that lack natural function. Here, we performed extensive single-cell transcriptomic analyses to map fate choices and gene expression patterns during hematopoietic differentiation of hPSCs and showed that oxidative metabolism was dysregulated during in vitro directed differentiation. Applying hypoxic conditions at the stage of endothelial-to-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 61 publications
(93 reference statements)
0
24
0
Order By: Relevance
“…Previous studies have shown that the hypoxia could drive the hematopoietic differentiation [ 15 ]. The occurrence of the EHT in vitro closely mimics how hematopoietic cells develop in vivo, although this process is accompanied by gradual downregulation of aerobic metabolism; however, it still remains in highly active aerobic metabolism when compared to those in vivo [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies have shown that the hypoxia could drive the hematopoietic differentiation [ 15 ]. The occurrence of the EHT in vitro closely mimics how hematopoietic cells develop in vivo, although this process is accompanied by gradual downregulation of aerobic metabolism; however, it still remains in highly active aerobic metabolism when compared to those in vivo [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the hypoxia could drive the hematopoietic differentiation [ 15 ]. The occurrence of the EHT in vitro closely mimics how hematopoietic cells develop in vivo, although this process is accompanied by gradual downregulation of aerobic metabolism; however, it still remains in highly active aerobic metabolism when compared to those in vivo [ 15 ]. To experimentally demonstrate the acquisition of the hematopoiesis under the hypoxia conditions, hESCs were therefore induced to differentiate into hematopoietic lineage under the hypoxia (5%) or the normoxia (21%) conditions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations